Clinical course and cost assessment of infants with a first episode of acute bronchiolitis presenting to the emergency department: Data from the GUERANDE clinical trial. Issue 12 (13th September 2021) - Butel, Thibault; Angoulvant, François; Filipovic‐Pierucci, Antoine; Milcent, Karen; Teglas, Jean‐Paul; Bellêttre, Xavier; Claudet, Isabelle; Gras‐le Guen, Christèle; de Pontual, Loïc; Minodier, Philippe; Dubos, François; Brouard, Jacques; et al.
Abstract: Introduction: Bronchiolitis is the leading cause of hospitalization for infants but its economic burden is not well documented . Our objective was to describe the clinical evolution and to assess the 1‐month cost of a first episode of acute bronchiolitis presenting to the emergency department (ED). Methods: Our study was an epidemiologic analysis and a cost study of the cohort drawn from the clinical trial GUERANDE, conducted in 24 French pediatric EDs. Infants of 6 weeks to 12 months of age presenting at pediatric EDs with a first episode of bronchiolitis were eligible. The costs considered were collected from a societal viewpoint, according to the recommendations of the French National Health Authority. Results: A total of 777 infants were included with a median age of 4 months. A total of 57% were hospitalized during the month following the first consultation in the ED, including 28 (3.6%) in an intensive care unit. The mean length of stay was 4.2 days (SD = 3.7). The average time to relief of all symptoms was 13 days (SD = 7). Average total cost per patient was €1919 (95% confidence interval: 1756–2138) from a societal perspective, mostly due to hospitalization cost. The estimated annual cost of bronchiolitis in infants was evaluated to be between €160 and €273 million in France. Discussion: Bronchiolitis represent a high cost for the health care system and broadly for society, with hospitalizations costs being the main cost driver. Thus significant investments should be made to develop innovative therapies, to reduce the number of hospitalizations and length of stay.